Molecular Tools for Monitoring Trichoderma in Agricultural Environments - Kredics, László; Chen, Liqiong; Kedves, Orsolya; Büchner, Rita; Hatvani, Lóránt; Allaga, Henrietta; Nagy, Viktor D.; Khaled, Jamal M.; Alharbi, Naiyf S.; Vágvölgyi, Csaba (Frontiers in Microbiology, 2018)
Various Trichoderma species possess significance in agricultural systems as biofertilizers or biocontrol agents (BCAs). Besides these beneficial features, certain Trichoderma species can also act as agricultural pests, causing the green mould disease of cultivated mushrooms. This double-faced nature of the genus in agricultural environments points at the importance of proper monitoring tools, which can be used to follow the presence and performance of candidate as well as patented and/or registered biocontrol strains, to assess the possible risks arising from their application, but also to track harmful, unwanted Trichoderma species like the green moulds in mushroom growing facilities. The objective of this review is to discuss the molecular tools available for the species- and strain-specific monitoring of Trichoderma, ranging from immunological approaches and fingerprinting tools to exogenous markers, specific primers used in polymerase chain reaction (PCR) as well as ‘omics’ approaches.